All-optical simultaneous AND & XOR logic gates based on nonlinear micro-ring resonator. Issue 21 (15th December 2018) - Mohebbi, Zahra; Nozhat, Najmeh; Khodadadi, Maryam
ABSTRACT: In this paper, we have proposed AND and XOR logic gates simultaneously in one structure. The presented structure is based on two-dimensional (2D) nonlinear photonic crystal with T–shaped waveguide and micro-ring resonator. In the proposed structure, the power consumption is2.5 × 10 7 W/m that is lower than similar logic gates and the extinction ratio is about 6.5 dB. Also, the switching time is attained to be 0.2 and 0.26 ps for AND and XOR logic gates, respectively. Simplicity and small size (18.4   µm×18.4 µm) of the structure make it suitable for photonic integrated circuits (PICs). All simulations are based on finite-difference time-domain (FDTD) and plane wave expansion (PWE) numerical methods.